KONSTRUKSI NARASI PEREMPUAN MENIKAH MUDA DI TIKTOK - Putri Rahayu, Salsabila; Claretta, Dyva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
One of the compelling issues on social media is the issue of early marriage. This is because, amid the marriage is scary phenomenon, the emergence of content about marriage is interesting to examine as an effort to counter the negative stigma surrounding the institution of marriage reflected in the marriage is scary trend. However, Azkia's early marriage content sparked controversy, as several narratives within it were considered to undermine the choices of other women who did not choose to marry young. What made this more troubling was that these narratives, which appeared to demean women's freedom in choosing their own life paths, were produced by Azkia as a fellow woman. This study aimed to analyze the narrative construction of young married women in Azkia's TikTok content using Sara Mills' Critical Discourse Analysis to identify subject and object positions as well as the audience's position. The results of this study showed that Azkia consistently occupied the position of active subject in discourse formation, while women who did not marry young those who pursued careers and focused on education occupied the object position. The conclusion drawn based on Sara Mills' Critical Discourse Analysis was that the narrative of young married women constructed in Azkia's TikTok content revealed a hidden discourse of patriarchal ideology and internalized misogynistic practices embedded within the narratives of Azkia's early marriage content.